Menelusuri Sejarah dan Beberapa Sastrawan Arab Penganut Aliran Simbolisme - Nur Illiyyin Setya Mufti (Tamaddun: Jurnal Kebudayaan dan Sastra Islam, 2023)
This research aims to explain the history and some prominent Arab literary figures who adhere to the symbolism literary movement, along with examples of their works. This study is a qualitative descriptive research using a literature review technique. The findings of this research indicate that the literary movement of symbolism first emerged in France in 1884. This movement is rooted in the belief that objects and events in the real world have profound meanings that can be expressed through symbolic language. Symbolist poetry is renowned for its deliberate ambiguity, designed to be mysterious and challenging to comprehend. Several Arab literary figures, such as Dr. Basyar Faris, Ali Ahmad Sa'id, Badr Syakir Sayyab, and Iliya Abu Madhi, also adopted this movement, blending it with their cultural context. The research discusses the shift from other literary movements to symbolism and the contributions of Arab writers in using natural symbols and myths to convey messages about human emotions and conditions.